BAC CLONES GENERATED FROM SHEARED DNA - Osoegawa, Kazutoyo (2006)
BAC libraries generated from restriction-digested genomic DNA display representational bias and lack some sequences. To facilitate completion of genome projects, procedures have been developed to create BACs from DNA physically sheared to create fragments extending up to 200 kb. The DNA fragments were repaired to create blunt ends and ligated to a new BAC vector. This approach has been tested by generating BAC libraries from Drosophila DNA, with average insert lengths between 50 – 150 kb. The libraries lack chimeric clone problems as determined by mapping paired BAC-end sequences to the assembled fly genome sequence. The utility of “sheared” libraries was demonstrated by closure of a previous clone gap and by isolation of clones from telomeric regions, which were notably absent from previous Drosophila BAC libraries.